Number 5 (November 1977) - E. C. Beckham (Southeastern Fishes Council Proceedings, 1977)
A report on the Escatawpa River System of Alabama and Mississippi. By E.C. Beckhan, 4 pp.
Keywords: fishes; Escatawpa River System